Inhibitory effects of Camellia japonica on cell inflammation and acute rat reflux esophagitis - Hyeon Hwa Nam; Li Nan; Byung Kil Choo (BMC, 2021)
Abstract Background Excessive and continuous inflammation may be the main cause of various immune system diseases. Reflux esophagitis (RE) is a common gastroesophageal reflux disease (GERD). Camellia japonica has high medicinal value and has long been used as a traditional herbal hemostatic medicine in China and Korea. The purpose of this study is to explore the antioxidant and anti-inflammatory activities of CJE and its protective effect on RE. Materials and methods Buds from C. japonica plants were collected in the mountain area of Jeju, South Korea. Dried C. japonica buds were extracted with 75% ethanol. DPPH and ABTS radical scavenging assay were evaluated according to previous method. The ROS production and anti-inflammatory effects of C. japonica buds ethanol extract (CJE) were evaluated on LPS-induced RAW 264.7 cell inflammation. The protective effects of CJE on RE were conducted in a RE rat model. Results CJE eliminated over 50% of DPPH and ABTS radical at concentration of 100 and 200 µg/mL, respectively. CJE alleviated changes in cell morphology, reduced production of ROS, NO and IL-1β. Also, down-regulated expression levels of iNOS, TNF-α, phosphorylated NF-κB, IκBα, and JNK/p38/MAPK. CJE reduced esophageal tissue damage ratio (40.3%) and attenuation of histological changes. In addition, CJE down-regulated the expression levels of TNF-α, IL-1β, COX-2 and phosphorylation levels of NF-κB and IκBα in esophageal tissue. Conclusions CJE possesses good anti-oxidation and anti-inflammatory activity, and can improve RE in rats caused by gastric acid reflux. Therefore, CJE is a natural material with good anti-oxidant and anti-inflammatory activity and has the possibility of being a candidate phytomedicine source for the treatment of RE.